Age and body mass index affect fit of spirometry Global Lung Function Initiative references in schoolchildren. Issue 2 (19th April 2022) - Mozun, Rebeca; Ardura-Garcia, Cristina; Pedersen, Eva S.L.; Usemann, Jakob; Singer, Florian; Latzin, Philipp; Moeller, Alexander; Kuehni, Claudia E.
Background: References from the Global Lung Function Initiative (GLI) are widely used to interpret children's spirometry results. We assessed fit for healthy schoolchildren. Methods: LuftiBus in the School was a population-based cross-sectional study undertaken in 2013–2016 in the canton of Zurich, Switzerland. Parents and their children aged 6–17 years answered questionnaires about respiratory symptoms and lifestyle. Children underwent spirometry in a mobile lung function lab. We calculated GLI-based z-scores for forced expiratory volume in 1 s (FEV1 ), forced vital capacity (FVC), FEV1 /FVC and forced expiratory flow for 25–75% of FVC (FEF25–75 ) for healthy White participants. We defined appropriate fit to GLI references by mean values between +0.5 and −0.5 z-scores. We assessed whether fit varied by age, body mass index, height and sex using linear regression models. Results: We analysed data from 2036 children with valid FEV1 measurements, of whom 1762 also had valid FVC measurements. The median age was 12.2 years. Fit was appropriate for children aged 6–11 years for all indices. In adolescents aged 12–17 years, fit was appropriate for FEV1 /FVC z-scores (mean±sd −0.09±1.02), but not for FEV1 (−0.62±0.98), FVC (−0.60±0.98) and FEF25–75 (−0.54±1.02). Mean FEV1, FVC and FEF25–75 z-scores fitted better in children considered overweight (−0.25, −0.13 and −0.38, respectively) than normal weight (−0.55, −0.50 and −0.55, respectively; p-trend <0.001, 0.014 and <0.001, respectively). FEV1, FVC and FEF25–75 z-scores depended on both age and height (p-interaction 0.033, 0.019 and <0.001, respectively). Conclusion: GLI-based FEV1, FVC, and FEF25–75 z-scores do not fit White Swiss adolescents well. This should be considered when using reference equations for clinical decision-making, research and international comparison. This study suggests GLI-based FEV1, FVC and FEF25–75% z-scores over-detect abnormal lung function in Swiss adolescents, and more so among slimmer adolescents, which has important implications for clinical care, research and international comparisons https://bit.ly/3sbGtAS